"RITE OF PASSAGE IN DIASPORA: JAMAICA KINCAID'S LUCY AS A POSTCOLONIAL KÜNSTLERROMAN" - Sayed Mohammed Youssef (European Scientific Journal, ESJ, 2015)
Jamaica Kincaid's novel Lucy (1990) is a coming-of-age story, or a Künstlerroman to be more specific in the tradition of James Joyce's A Portrait of the Artist as a Young Man (1917), that simply revolves around a young woman artist, who learns much from the school of life and personal experiences other than from ordinary education at academic institutions. The eponymous protagonist breaks away from such forces as colonial and patriarchal mores, which eventually contributes to her construction of her own hybrid identity and inaugurates her maturity. This struggle is established perfectly well through her apparent resistance to the constraints primarily imposed on her race and gender by both the Eurocentric society, which she has just left behind at home, and the androcentric society she encounters in diaspora. Surprisingly enough, Lucy, who is chastened towards the end of the book, creates her rite of passage towards development and independence through her valiant efforts to overcome such confines at any cost. The aim of the present article is to analyse the young artist's character formation and growth both at home and in diaspora from a postcolonial perspective. This way, it intertwines discussions of transition from innocence to experience along with such elements as androcentrism, colonial and postcolonial rebellion, and questions of identity, hybridity, diaspora and cultural displacement, which are all inextricably linked with the postcolonial discourse.